Interaction of Graphene Oxide Particles and Dendrimers with Human Breast Cancer Cells by Real-Time Microscopy - Ribeiro, Beatriz Fumelli Monti; Chaves, Julyane Batista; De Souza, Marcelo Medina; Keppler, Artur Franz; Do Carmo, Devaney Ribeiro [UNESP]; Machado-Santelli, Gláucia M. (MDPI, 2023)
Graphene oxide (GOX) has become attractive due to its unique physicochemical properties. This nanomaterial can associate with other dendrimers, making them more soluble and allowing better interaction with biomacromolecules. The present study aimed to investigate, by real-time microscopy, the behavior of human breast cancer cells exposed to particles of materials based on graphene oxide. The MCF-7 cell line was exposed to GOX, GOX associated with Polypropylenimine hexadecaamine Dendrimer, Generation 3.0—DAB-AM-16 (GOXD) and GOX associated with polypropyleneimine—PAMAM (GOXP) in the presence or absence of fetal bovine serum (FBS). GOX, GOXD and GOXP were taken up by the cells in clusters and then the clusters were fragmented into smaller ones inside the cells. Real-time microscopy showed that the presence of FBS in the culture medium could allow a more efficient internalization of graphene materials. After internalizing the materials, cells can redistribute the clumps to their daughter cells. In conclusion, the present study showed that the particles can adhere to the cell surface, favoring their internalization. The presence of FBS contributed to the formation of smaller aggregates of particles, avoiding the formation of large ones, and thus transmitted a more efficient internalization of the materials through the interaction of the particles with the cell membrane.
Keywords: breast cancer cell culture; graphene; nanoparticles internalization; real-time microscopy